Decoupling Abundance and Biomass of Phytoplankton Communities Under Different Environmental Controls: A New Multi-Metric Index - Ní Longphuirt, Sorcha; McDermott, Georgina; O’Boyle, Shane; Wilkes, Robert; Stengel, Dagmar Brigitte (Frontiers in Marine Science, 2019)
Increased nutrient delivery to estuarine systems results in elevated growth of primary producers. This is evidenced by high chlorophyll concentrations and increased frequency of phytoplankton blooms. However, shifts in nutrient loads to estuarine ecosystems can also cause modifications in the structure of phytoplankton communities which can have adverse impacts right through the food web. Acknowledging these modifications is imperative if response mechanisms are to be fully understood. In this study, Ireland’s current water framework directive (WFD) tool for determining the status of phytoplankton communities was built upon to encompass not only biomass and bloom frequency but also community structure (diversity and evenness) and abundance. This method allows for comparison with site- and date-specific environmental data which could give an indication of cause and effect relationships. The newly developed phytoplankton index performed well against current methods to determine ecological status. Furthermore, it had a better agreement with other physico-chemical and biological WFD parameters. Statistical analysis captured the relationship between the phytoplankton index and physico-chemical parameters, allowing for a more detailed look at the impact of disturbance on the system. The inclusion of community structure acknowledged the imbalances in the phytoplankton communities of some systems even when frequent blooms are not evident. In bloom conditions, the disparity between the chlorophyll and abundance metrics within the phytoplankton index can be linked to winter dissolved inorganic nitrogen concentra- tion and forms, temperature, and light conditions. Application of the phytoplankton index will allow not only for compliance with WFD requirements, but also a method for understanding and assessing ecosystem health of estuarine phytoplankton communities over spatial and temporal timelines in line with changes in physiochemical parameters.